Matkailun markkinointi sosiaalisessa mediassa - Vatanen, Jessi (2019)
This study concentrates on how social media is affecting tourism marketing. First this study describes a general picture of tourism and social media marketing. Next tourism marketing in social media was considered more closely. Impacts of social media to tourism were examined from perspectives of users and tourism industry operators. At the end of the study it was considered what possibilities and potential challenges are related to social media use in tourism and tourism marketing. Central goals of this study were to make it clear how tourism marketing in social media has been researched and has social media impacted to tourism marketing. Also, one of the main goals was to consider how travelers and tourism companies use social media for tourism. The study was made as a literature review. Sources of this study were related to tourism in general as well as social media use related to tourism. There are some contradictory results from the benefits of social media to tourism. Research shows that user-generated content, targeted marketing, user engagement, and involvement in social media can be used to create new opportunities for tourism marketing. However, measuring direct benefits has been found to be challenging. Social media and its development have forced the tourism industry to adapt to the reforms it brought. For example, user-generated content plays a significant role in planning and booking trips.